BI 1015550 is a PDE4B Inhibitor and a Clinical Drug Candidate for the Oral Treatment of Idiopathic Pulmonary Fibrosis - Herrmann, Franziska Elena; Hesslinger, Christian; Wollin, Lutz; Nickolaus, Peter (Frontiers in Pharmacology, 2022)
The anti-inflammatory and immunomodulatory abilities of oral selective phosphodiesterase 4 (PDE4) inhibitors enabled the approval of roflumilast and apremilast for use in chronic obstructive pulmonary disease and psoriasis/psoriatic arthritis, respectively. However, the antifibrotic potential of PDE4 inhibitors has not yet been explored clinically. BI 1015550 is a novel PDE4 inhibitor showing a preferential enzymatic inhibition of PDE4B. In vitro, BI 1015550 inhibits lipopolysaccharide (LPS)-induced tumor necrosis factor- (TNF) and phytohemagglutinin-induced interleukin-2 synthesis in human peripheral blood mononuclear cells, as well as LPS-induced TNF synthesis in human and rat whole blood. In vivo, oral BI 1015550 shows potent anti-inflammatory activity in mice by inhibiting LPS-induced TNF synthesis ex vivo and in Suncus murinus by inhibiting neutrophil influx into bronchoalveolar lavage fluid stimulated by nebulized LPS. In Suncus murinus, PDE4 inhibitors induce emesis, a well-known gastrointestinal side effect limiting the use of PDE4 inhibitors in humans, and the therapeutic ratio of BI 101555 appeared to be substantially improved compared with roflumilast. Oral BI 1015550 was also tested in two well-known mouse models of lung fibrosis (induced by either bleomycin or silica) under therapeutic conditions, and appeared to be effective by modulating various model-specific parameters. To better understand the antifibrotic potential of BI 1015550 in vivo, its direct effect on human fibroblasts from patients with idiopathic pulmonary fibrosis (IPF) was investigated in vitro. BI 1015550 inhibited transforming growth factor-β-stimulated myofibroblast transformation and the mRNA expression of various extracellular matrix proteins, as well as basic fibroblast growth factor plus interleukin-1β-induced cell proliferation. Nintedanib overall was unremarkable in these assays, but interestingly, the inhibition of proliferation was synergistic when it was combined with BI 1015550, leading to a roughly 10-fold shift of the concentration–response curve to the left. In summary, the unique preferential inhibition of PDE4B by BI 1015550 and its anticipated improved tolerability in humans, plus its anti-inflammatory and antifibrotic potential, suggest BI 1015550 to be a promising oral clinical candidate for the treatment of IPF and other fibro-proliferative diseases.